Awe Enhances Creative Thinking: An Experimental Study. Issue 2 (3rd April 2018) - Chirico, Alice; Glaveanu, Vlad Petre; Cipresso, Pietro; Riva, Giuseppe; Gaggioli, Andrea
Abstract : Awe is a complex emotion characterized by feelings of vastness and a need for accommodation. The aim of this study was to investigate whether the experience of awe impacts on peculiar dimensions of creative potential in terms of creative thinking. Fifty-two university students were exposed both to an awe-inducing 3D-video and to a neutral one in a within-subject design. After each video, participants reported the intensity and type of perceived emotion and completed two verbal tasks of the Torrance Tests of Creative Thinking (TTCT; Torrance, 1974). A direct causal relationship between awe and creative thinking was tested using generalized linear model. Results showed that awe affected key creative thinking components—fluency, flexibility and elaboration measured by the product improvement test—compared to the neutral stimulus. Implications of these findings for future research and limitations are discussed.